Advanced metering infrastructure smart metering based on cloud architecture for low voltage distribution networks in application of smart grid monitoring - Alassery, Fawaz (Sustainable computing informatics and systems, 2022)
In most circumstances, accessing measurements from entire smart metres set in less-voltage grid area for distribution monitoring is not practicable because of less bandwidth as well as excessive delays in accessing Smart Meter monitoring. Estimating the condition of a distribution system can be done using voltage, active and reactive power measurements from smart metres subset. On one hand, increasing number of selected smart metres improves distribution state assessment accuracy, it degrades monitoring data time. It improves the electrical system's dependability and efficiency while also providing security to the system. Smart grid infrastructure is a modified form of smart grid. Smart grid infrastructure is a modified form of the smart grid. It has high-capacity converters, sensing and metering technologies, and automated control to improve efficiency and dependability. The goal of this article is to use smart metering technology to improve the observer of low-voltage distribution grids. The use of a distribution network-based state estimation technique employing smart metre readings for near-real-time monitoring of low-voltage distribution grids is the focus of this research. This paper propose smart metering based on cloud architecture for low voltage distribution networks with distribution network based state estimation algorithm in application of monitoring. The article will discuss the critical role of cloud solution in achieving interoperability, scalability and flexibility as well as enabling integration of various services for distribution system automation. As an example of coordinated operation of diverse distribution grid services by cloud, distributed state estimation technique as well as autonomous network reconfiguration will be demonstrated. •The goal of this article is to use smart metering technology to improve the observability of low-voltage distribution grids.•To deal with estimating grid voltages with reasonable accuracy using a state estimate technique that employs smart meter data.•Here proposed architecture enhanced issue of enhancing low-voltage distribution grids observability using smart metering infrastructure.•The experimental results show comparative analysis for various distributed network types and technique based comparison between existing and proposed technique.